Arcabouço cronoestratigráfico da Formação Mafra (intervalo médio) na região de Rio Negro/PR - Mafra/SC, borda leste da bacia do Paraná - Weinschütz, Luiz Carlos [UNESP]; Castro, Joel Carneiro De [UNESP] (Escola de Minas, 2004)
The middle interval of Mafra Formation (Itararé Group) has been investigated in the Mafra-Rio Negro area, eastern margin of Paraná basin. The 40m-cored section of well PM-6, drilled at the foot of the 70m-high Motocross Quarry, provide a 90m-composite column representative of middle-Mafra Formation. This interval is unconformably overlain by sigmoidal sandstones of the upper part of Mafra Formation, as displayed in the same quarry. Two types of cycles are found in middle Mafra. Several coarsening-upward cycles composed of varvites, massive sandstones/siltstones (local) and diamictites, are followed by a major fining-upward cycle, formed by sandstone, diamictite and varvite. Pebble to boulder-size dropstones occur in all facies. The upper FU-cycle, designated as deglaciation facies/cycle, has a complex distribution of thickness and constituent lithofacies. Local depocenters of the cycle are related to lows escavated by glaciers; they were filled by sediments derived from the receeding ice, in a classical, transgressive setting related to deglaciation. The middle-Mafra Formation forms the upper, transgressive-highstand system tracts of a depositional sequence, together with sandstones and diamictites of the lower, lowstand system tracts of lower Mafra Formation.

Esse trabalho investiga a porção média da Formação Mafra (Grupo Itararé) na região de Mafra(SC)-Rio Negro(PR). Uma sondagem com 40m testemunhados (PM-6), adjacente a uma grande pedreira com 70m de altura, fornece, em conjunto, quase 100m de seção, dominada por varvitos e diamictitos, representativa do Mafra-Médio. Recobrindo erosivamente esse intervalo, a mesma pedreira expõe 20m de arenitos sigmoidais, já caracterizando a unidade Mafra-Superior. A Formação Mafra-Médio consiste de ciclos de granocrescência ascendente (varvito a diamictito), recobertos por um complexo ciclo granodecrescente (arenito-diamictito-varvito), atribuído a eventos de deglaciação; esse evento culmina com a deposição de siltito fossilífero marinho, que, ao contrário das demais fácies, não tem clastos caídos (dropstones). As complexas relações laterais que marcam o ciclo/evento de deglaciação podem ser documentadas em uma seção estratigráfica com cinco afloramentos. A base do evento é erosiva, fornecendo calhas que acomodam localmente grandes espessuras; tal sucessão transgressiva, desenvolvida com a deglaciação, deve-se ao recuo progressivo das geleiras. O intervalo médio da Formação Mafra representa um trato de sistemas transgressivo/de nível de base alto de uma seqüência deposicional de 3ª ordem, junto com os arenitos e siltitos do Mafra-Inferior, estes constituindo o trato de sistemas de nível baixo.
Keywords: Glacial Sedimentation; Sequence Stratigraphy; Itararé Group; Paraná Basin; Permocarboníferous; Sedimentação Glacial; Estratigrafia de Seqüências; Grupo Itararé; Bacia do Paraná; Permocarbonífero